2011
DOI: 10.1182/blood-2010-08-304683
|View full text |Cite
|
Sign up to set email alerts
|

Fludarabine, cyclophosphamide, and rituximab chemoimmunotherapy is highly effective treatment for relapsed patients with CLL

Abstract: Optimal management of patients with relapsed/refractory chronic lymphocytic leukemia (CLL) is dictated by patient characteristics, prior therapy, and response to prior therapy. We report the final analysis of combined fludarabine, cyclophosphamide, and rituximab (FCR) for previously treated patients with CLL and identify patients who benefit most from this therapy. We explore efficacy of FCR in patients beyond first relapse, patients with prior exposure to fludarabine and alkylating agent combinations, and pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
122
3
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(135 citation statements)
references
References 32 publications
4
122
3
6
Order By: Relevance
“…While the latter features did not have prognostic predictivity at multivariate analysis in this clinically aggressive population, our study demonstrated that the histopathological pattern defined by the presence of confluent PCs may represent an important feature for risk assessment in this subset of patients. This finding is important when considering that increasing awareness of the possible evolution into Richter's syndrome is prompting clinicians to perform lymph node biopsy more often than in the past, 45 and that the therapeutic armamentarium in clinically aggressive CLL may include intensive chemoimmunotherapy 46 and allogeneic bone marrow transplantation from HLA-identical siblings and well-matched unrelated donors. 47,48 …”
Section: Discussionmentioning
confidence: 99%
“…While the latter features did not have prognostic predictivity at multivariate analysis in this clinically aggressive population, our study demonstrated that the histopathological pattern defined by the presence of confluent PCs may represent an important feature for risk assessment in this subset of patients. This finding is important when considering that increasing awareness of the possible evolution into Richter's syndrome is prompting clinicians to perform lymph node biopsy more often than in the past, 45 and that the therapeutic armamentarium in clinically aggressive CLL may include intensive chemoimmunotherapy 46 and allogeneic bone marrow transplantation from HLA-identical siblings and well-matched unrelated donors. 47,48 …”
Section: Discussionmentioning
confidence: 99%
“…Responses in patients with 17pdel/TP53 mutation were consistent (57%), comparing favorably to regimens including anti-CD20 monoclonal antibody therapy either with FC (35%) 12 or B (rituximab 7.1%, ofatumumab 37%).…”
mentioning
confidence: 89%
“…In the MD Anderson Cancer Center experience responses after FCR were affected by the type of previous treatment. 12 As mentioned above, number and quality of responses were unaffected by previous type and number of lines of therapy, although 38% patients had previously received FCR. Furthermore, after BenCam, compared to FCR we recorded similar responses in 11q del cases and confirmed the favorable impact of alemtuzumab combining treatment in patients showing trisomy 12.…”
mentioning
confidence: 93%
“…However, a recent report of 284 relapsed patients treated with FCR that did consider refractory patients separately found that those who were fludarabine refractory had a complete remission (CR)/nodular partial remission (nPR) rate of only 8% (ORR 56%), compared with 46% for other patients previously exposed to fludarabine and alkylators. 10 In multivariable analysis, fludarabinerefractory disease was a significant predictor of short PFS and OS, along with 17p deletion and complex karyotype, among others, 10 leading the investigators to conclude that FCR is most appropriate for fludarabine-sensitive patients with up to 3 prior regimens and without 17p abnormalities. Other regimens with described activity in fludarabine-refractory CLL include CFAR (FCR plus alemtuzumab) and OFAR (oxaliplatin, fludarabine, cytarabine, rituximab), but results are not clearly better than FCR in this group (Table 1).…”
Section: Approach To the Cit-refractory Cll Patientmentioning
confidence: 99%